JENIS PAKAN MEMPENGARUHI PRODUKSI BIOGAS DARI FESES GAJAH, STUDI KASUS GAJAH SUMATERA (Elephas maximus sumatranus Temminck, 1847) DI TAMAN MARGASATWA RAGUNAN, JAKARTA SELATAN - Fuad Albani; Megga Ratnasari Pikoli; Irawan Sugoro (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2018)
Elephant dung is a source of methane gas, which the gas is the main contributor to greenhouse gas if not used as fuel. Wild elephants use grass leaves as their feed, but in Ragunan Wildlife Park, elephants are fed also with a combination of elephant grass, sweet potatoes, maize, and bananas, which aim to meet immediate nutritional needs and ensure their health. Therefore, this study examined the biogas production of elephant feces associated with the feed given. The purpose of this study is to investigate the contribution of biogas that is emitted from the elephant feces as a result of two kinds of feed, which were elephant grass and combination of elephant grass, sweet potatoes, maize, and bananas. Previously, the elephants were acclimatized for 4 days with the two types of feed. Fermentation of the feces was conducted by using simple fermenters by volume of 3.42 L for 28 days and performed measurements of temperature, pH, concentration of ammonia, concentration of volatile fatty acids, substrate degradation and production of biogas. The result showed that the composition of feed affects the physico-chemical characteristics of the feces, production of ammonia and volatile fatty acids, substrate degradation and production of biogas.  The feces of Sumatran elephant fed with elephant grasses has higher potential for decomposition to mineralization into biogas and produce a higher proportion of methane gas carbon dioxide, than those fed with the combinated feed. This result needs to be a concern because with the fiber-rich feed like in their natural habitats, elephants have the potential to emit higher gas emissions. Therefore the biogas released from the elephant feces or other animals should be processed and utilized to meet the energy needs in the wildlife park itself.